Letter from S.B. Brown to James Curtis Booth - Brown, S. B. (1884)
Letter from S. B. Brown to James Curtis Booth (1810-1888) with the "receipt for Mr. Kirk as requested."
Keywords: Booth, James Curtis, 1810-1888